Bridging the Language Gap in Medicine: Quality Improvement for Interpreter Services at JayDoc Free Clinic - Skyler Trieu; Shilpika Bajpai (Journal of Student-Run Clinics, 2022)
Background: JayDoc Free Clinic (JayDoc) is run by medical students at the University of Kansas School of Medicine. Many patients seen at the clinic have limited English proficiency (LEP) and are assisted by volunteer medical interpreters. Formal training for working with interpreters has not previously been part of JayDoc’s volunteer orientation.Methods: An intervention emphasizing education in interpreter standards of practice, effective use of interpreter services, and culturally competent communication were presented to all incoming JayDoc volunteers (i.e., first-year medical students [MS1s]) during their volunteer orientation. Three months post-intervention a voluntary online survey was distributed to assess perceived improvement in effective interpreter partnerships and cultural communication. The survey was administered to MS1s and second-year medical students (MS2s). Responses were stratified using a two-tailed t-score distribution to analyze the impact of the educational intervention on the MS1 group in comparison to the MS2 group that did not receive the intervention.Results: There were one hundred and five respondents (52 MS1s, 53 MS2s). MS2s had a significantly higher average number of interpreter-facilitated patient encounters (MS2 6.38; MS1 2.54; p=0.001). MS1s had a significantly higher average of perceived importance of interpreter training (MS2 4.56; MS1 4.81; p=0.031). All other survey parameters of cultural competency and interpreter-provider best practices were ranked as important by both MS1s and MS2s, without a significant difference between the responses of the two groups.Conclusions: An educational intervention focused on interpreter-provider partnerships and cultural competency resulted in the higher perceived importance of the training session among students.